2019
DOI: 10.1037/dec0000097
|View full text |Cite
|
Sign up to set email alerts
|

What’s in a response time?: On the importance of response time measures in constraining models of context effects.

Abstract: Context effects are phenomena of multiattribute, multialternative decision-making that contradict normative models of preference. Numerous computational models have been created to explain these effects, communicated through the estimation of model parameters. Historically, parameters have been estimated by fitting these models to choice response data alone. In other contexts, such as those conventionally studied in perceptual decision-making, the times associated with choice responses have proven effective in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 51 publications
(115 reference statements)
1
8
0
Order By: Relevance
“…To provide some indication of whether or not statistics are sufficient for models of choice-response time, one can compare estimated posterior distributions under two conditions: fitting the model using quantiles, and fitting the model using the full set of data. If the two posteriors closely align, then the set of summary statistics could be declared as jointly sufficient for the parameters of the model under consideration (Molloy, Galdo, Bahg, Liu, & Turner, 2019). Turner and Sederberg (2014) demonstrated using the LBA model (which has a tractable likelihood function) that quantiles are not jointly sufficient for the LBA parameters, and thus do not convey the same information as the full choice-response time distribution when fitting the model to data.…”
Section: Discussionmentioning
confidence: 99%
“…To provide some indication of whether or not statistics are sufficient for models of choice-response time, one can compare estimated posterior distributions under two conditions: fitting the model using quantiles, and fitting the model using the full set of data. If the two posteriors closely align, then the set of summary statistics could be declared as jointly sufficient for the parameters of the model under consideration (Molloy, Galdo, Bahg, Liu, & Turner, 2019). Turner and Sederberg (2014) demonstrated using the LBA model (which has a tractable likelihood function) that quantiles are not jointly sufficient for the LBA parameters, and thus do not convey the same information as the full choice-response time distribution when fitting the model to data.…”
Section: Discussionmentioning
confidence: 99%
“…Second, our study overlooked the record of response times. According to a research by Molloy et al (2019), different categories of context effects tend to be observed at different points of time after the stimuli appear. The present research paid attention to the distance and response button but neglected the importance of recording response times.…”
Section: General Discussion and Conclusionmentioning
confidence: 99%
“…Recently, there have been several algorithmic advancements that have addressed the problem of correlated dimensions (Carpenter et al, 2017; Neal, 2011; Turner, Sederberg et al, 2013). One example that will be featured throughout this article is differential-evolution MCMC (DEMCMC; ter Braak, 2006), which has now been productively applied to a wide range of models in psychology (Evans, Steyvers, & Brown, 2018; Heathcote et al, 2019; Molloy, Galdo, Bahg, Liu, & Turner, 2019; Turner, Sederberg et al, 2013). The main difference between DEMCMC and MCMC is the manner in which the two algorithms search the parameter space.…”
Section: Current Bayesian Methodsmentioning
confidence: 99%